RESEARCH TREND OF WORKING CAPITAL MANAGEMENT - Rahmawati, Sisca Dian; Lamidi; Zakiyah, Nadiya Fikriyatus; Murningsih, Setia; Putra, Febrianur Ibnu Fitroh Sukono (Universitas Sains dan Teknologi Komputer, 2024)
Given the importance of working capital in firm dynamics, the main objective of this research is to highlight the main gaps and insights in the working capital literature and suggest future research, as well as to know the development trend of working capital management research published by leading journals. For this reason, a bibliometric analysis was carried out using bibliographic information from Scopus for the topic